Effect of medium composition and temperature and pH changes on exopolysaccharide yields and stability during Streptococcus thermophilus LY03 fermentations - Degeest, Bart (2002)
To increase the exopolysaccharide (EPS) yields from Streptococcus thermophilus LY03 and to unravel the nature of the EPS degradation process, fermentation experiments were carried out with this strain in a customized MRS medium, using different additional carbohydrates or amino acids possibly related to growth and EPS production. No significant increase of the EPS yields or activities of the enzymes α-phosphoglucomutase, UDP-glucose pyrophosphorylase and UDP-galactose 4-epimerase that are correlated with EPS production, or of the activity of dTDP-glucose pyrophosphorylase involved in the rhamnose synthetic branch of EPS biosynthesis, was observed. The EPS monomer composition remained unchanged for all experiments. Fermentations with a sudden temperature increase or lowered pH were carried out as well to try to avoid EPS degradation upon prolonged fermentation. It was demonstrated that EPS degradation took place enzymatically. Incubations of purified high-molecular-mass EPS with cell-free culture supernatant or cell extracts showed its degradation by enzymes with an endo-activity. This glycohydrolytic activity probably encompasses several enzymes having a molecular mass lower than 50,000 and 10,000 Da, and seems to be rather stable at high temperature and low pH. These results contribute to a better understanding of the physiological and chemical factors influencing EPS production and degradation.